Arterial Stiffness in Chronic Kidney Disease: The Usefulness of a Marker of Vascular Damage - Antonio Bellasi; Emiliana Ferramosca; Carlo Ratti (International Journal of Nephrology)
Increased arterial stiffness is a marker of vasculopathy in chronic kidney disease (CKD) patients, suggesting a significant cardiovascular damage. Detection of arterial stiffness provides physicians with useful prognostic information independent of traditional cardiovascular (CV) risk factors. In addition, this knowledge may help guide appropriate therapeutic choices and monitor the effectiveness of antihypertensive therapies. We review the relationship between arterial stiffness and CKD, as well as the prognostic implications of increased arterial stiffness and the potential therapeutic strategies to ameliorate arterial compliance and outcome in CKD.